2014
DOI: 10.1002/prp2.18
|View full text |Cite
|
Sign up to set email alerts
|

Nigramide J is a novel potent inverse agonist of the human constitutive androstane receptor

Abstract: The constitutive androstane receptor (CAR, NR1I3) is very important for drug development and for understanding pharmacokinetic drug–drug interactions. We screened by mammalian one hybrid assay among natural compounds to discover novel ligands of human constitutive androstane receptor (hCAR). hCAR transcriptional activity was measured by luciferase assay and mRNA levels of CYP2B6 and CYP3A4 in HepTR-hCAR cells and human primary hepatocytes were measured by real-time RT-PCR. Nigramide J (NJ) whose efficacy is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…NigC at concentrations of up to 10 mM had no effect on the basal transactivity of hCAR (Supplemental Fig. 1 and our previous report, Kanno et al, 2014). Furthermore, we investigated whether NigC could reverse inverse agonist-mediated suppression.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…NigC at concentrations of up to 10 mM had no effect on the basal transactivity of hCAR (Supplemental Fig. 1 and our previous report, Kanno et al, 2014). Furthermore, we investigated whether NigC could reverse inverse agonist-mediated suppression.…”
Section: Resultsmentioning
confidence: 70%
“…These observations indicate that NigC is not a ligand of hCAR. It is notable that compound 3 (NigJ), which differs in its structure from 1 by only C-6 aliphatic moiety, has been identified as a potent inverse agonist of hCAR (Kanno et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…and PBREM-Luc reporter assays. However, our previous report showed that CITCO can reverse inverse agonistmediated CAR repression (Kanno et al, 2014). These observations suggest that CITCO has high affinity, but weak inverse agonistic activity.…”
Section: Discussionmentioning
confidence: 90%
“…pIRES-puro/human PXR (hPXR) was constructed by inserting an hPXR fragment, which was amplified from cDNA of HepG2 cells by polymerase chain reaction, into the pIRES-puro vector (Clontech Laboratories, Inc., Palo Alto, CA). The construction of expression plasmids for GAL4/DNAbinding domain (DBD)-fused human CAR (hCAR)/ligand binding domain (LBD) (GAL4/DBD-hCAR/LBD), GAL4/DBD-hCAR/LBD + three amino acid (+3 a.a.), and GAL4/DBD-hPXR/LBD has been reported previously (Kanno and Inouye, 2010;Kanno et al, 2014). Preparation of the hCAR (pcDNA5-hCAR) expression plasmid and penobarbital-responsive enhancer module (PBREM)-driven luciferase reporter plasmid (PBREM-Luc) has also been described previously (Kanno et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation